2004
DOI: 10.1016/j.ympev.2003.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting phylogenies of balsaminoid families and the polytomy in Ericales: combining data in a Bayesian framework

Abstract: The balsaminoid Ericales, namely Balsaminaceae, Marcgraviaceae, Tetrameristaceae, and Pellicieraceae have been confidently placed at the base of Ericales, but the relations among these families have been resolved differently in recent analyses. Sister to this basal group is a large polytomy comprising all other families of Ericales, which is associated with short internodes. Because there are more than 13 kb of sequences for a large sampling of representatives, a thorough examination of the available data with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 75 publications
2
79
2
1
Order By: Relevance
“…The balsaminoid clade was first identified in a molecular study by Morton et al (1996) and is one of the few larger ericalean clades that repeatedly has found strong support in phylogenetic studies dealing with the order (Källersjö et al 1998;Anderberg et al 2002;Bremer et al 2002;Geuten et al 2004;Schö nenberger et al 2005). Interfamilial relationships in the clade, however, are problematic, apparently because of conflicting phylogenetic signals from chloroplast and mitochondrial data (Geuten et al 2004;Schö nenberger et al 2005). The clade comprises ca 1136 species in 12 genera.…”
Section: Resultsmentioning
confidence: 99%
“…The balsaminoid clade was first identified in a molecular study by Morton et al (1996) and is one of the few larger ericalean clades that repeatedly has found strong support in phylogenetic studies dealing with the order (Källersjö et al 1998;Anderberg et al 2002;Bremer et al 2002;Geuten et al 2004;Schö nenberger et al 2005). Interfamilial relationships in the clade, however, are problematic, apparently because of conflicting phylogenetic signals from chloroplast and mitochondrial data (Geuten et al 2004;Schö nenberger et al 2005). The clade comprises ca 1136 species in 12 genera.…”
Section: Resultsmentioning
confidence: 99%
“…Although many earlier studies at family level or above showed that Balsaminaceae are part of the basal clade in Ericales, the use of only very few Impatiens species in those surveys could not provide a definite answer regarding the monophyly of the family Soltis et al 2000;Albach et al 2001;Anderberg et al 2002;Bremer et al 2002;APG 2003;Geuten et al 2004). Yuan et al (2004) included adequate taxon sampling to test and affirm the monophyly of Balsaminaceae.…”
Section: Discussionmentioning
confidence: 98%
“…Fresh material, silica dried specimens, and herbarium specimens of 86 Impatiens species are used in this molecular study. Recent molecular results confirmed a well supported clade of Tetrameristaceae and Marcgraviaceae with Balsaminaceae (Morton et al 1996;Savolainen et al 2000;Soltis et al 2000;Albach et al 2001;Anderberg et al 2002;Bremer et al 2002;APG 2003;Geuten et al 2004). Therefore, we used representatives of Marcgraviaceae (Marcgravia umbellata, M. maguire, Norantea guianensis, Souroubea sp.…”
Section: Methodsmentioning
confidence: 95%
“…Amplification reactions were carried out on a GeneAmp PCR system 9700 (Applied Biosystems). Cycle sequencing reactions were performed as in Geuten et al (2004).…”
Section: Molecular Protocolsmentioning
confidence: 99%
“…According to the phylogeny of the cloned AP3/DEF-like genes, MuDEF is sister of both Impatiens copies, suggesting the occurrence of a duplication in the AP3/DEF lineage subsequent to the divergence of Marcgraviaceae and Balsaminaceae. Impatiens is one of the two genera belonging to the Balsaminaceae family, which is considered to be closely related to the neotropical Marcgraviaceae Bremer et al, 2002;Geuten et al, 2004;Schö nenberger et al, 2005).…”
Section: Introductionmentioning
confidence: 99%